Menghadapi Tantangan Zaman: Peran dan Strategi Pola Asuh Orang tua dalam Membentuk Karakter Anak di Era Digital - Helma Winda (4, 2024)
The rapid development of technology in the current digital era has caused the values ​​that are born, both positive and negative, to experience extraordinary shocks for humans. From this shock, the role of parents in educating their children has also changed in accordance with the development of the times. In the 80s, parents in educating their children must have experienced differences compared to the current digital era. Parenting patterns that initially only applied authoritarian, permissive, or democratic parenting patterns have experienced success in educating children. However, in the digital era, the three parenting patterns will not be successful if they do not synchronize according to the situation and conditions in terms of raising children. The method used in this study is a qualitative method in document studies. The intended document study is a study that searches for literature in accordance with study materials such as books, articles, the internet and so on. The results of this study show the importance of the active role of parents in directing their children's use of technology, as well as the need for a structured strategy to ensure that children grow up with strong and positive characters amidst the challenges of the digital era. Abstrak Perkembangan teknologi yang semakin pesat di era digital sekarang ini menyebabkan nilai-nilai yang dilahirkan, baik positif maupun negatif, ikut mengalami kejutan yang luar biasa bagi manusia. Dari kejutan tersebut, peran orang tua dalam mendidik anaknya ikut mengalami perubahan sesuai dengan perkembangan zaman. Di era 80-an, orang tua dalam mendidik anaknya pasti mengalami perbedaan dibandingkan dengan era digital saat ini. Pola asuh orang tua yang pada awalnya hanya menerapkan tipe pola asuh otoriter, permisif, atau demokratis, telah mengalami keberhasilan dalam mendidik anak. Namun, di era digital, ketiga pola asuh tersebut tidak akan berhasil jika tidak melakukan sinkronisasi sesuai dengan situasi dan kondisi dalam hal mengasuh anak. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dalam kajian dokumen. Kajian dokumen yang dimaksud adalah kajian yang mencari literatur sesuai dengan bahan kajian seperti buku, artikel, internet dan lain sebagainya. Hasil penelitian ini menunjukkan pentingnya peran aktif orang tua dalam mengarahkan penggunaan teknologi anak-anak mereka, serta perlunya strategi yang terstruktur untuk memastikan anak-anak tumbuh dengan karakter yang kuat dan positif di tengah tantangan era digital.